Short enantioselective synthesis of guggultetrol, a naturally occurring lipid - George, Shyla; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2010)
An enantioselective synthesis of the naturally occurring lipid, guggultetrol, is described with an overall yield of 24% starting from commercially available 1-pentadecanol in ten linear steps. The key chiral-inducing steps include a Sharpless asymmetric epoxidation of allylic alcohol and a dihydroxylation of an alpha,beta-unsaturated ester. (C) 2010 Elsevier Ltd. All rights reserved.